Universal Ultrasound Screening for Developmental Dysplasia of the Hip Among Infants in Community Settings in Japan: A Scoping Review - Asa Inagaki-Asano; Chikako Honda; Hiroshige Matsumoto; Kyoko Yoshioka-Maeda (SAGE Publishing, 2024)
Introduction Early identification of developmental dysplasia of the hip (DDH) is necessary to minimize its negative effects. Ultrasound screening is useful for detecting DDH in hospitals. Awareness about community-based screening systems is low in Japan. Despite established nationwide home visiting services and child health checkups in the country, more than 10% of DDH patients are diagnosed at the age of ≥1 year. This review aimed to clarify the status of universal ultrasound screening for DDH among infants in community settings in Japan. Methods The electronic databases of Igaku Chuo Zasshi, MEDLINE, CHINAL, ERIC, and APA PsycInfo were searched for articles published between 2002 and 2022. Articles were evaluated with the reach, effectiveness, adoption, implementation, and maintenance framework. Results In total, 148 articles were identified. Two articles were manually added, and 67 articles were excluded through abstract reviews, of which 20 were duplicates. Finally, 18 articles were included in the analysis. There are two types of universal ultrasound screening in community settings: municipality-led and hospital-led. Since 1992, municipality-led screening has been conducted during public infant health checkups in five municipalities. Six hospitals implemented ultrasound screening. The participation rate was around 90%. The Graf method is typically used for this purpose. The prevalence of abnormal hips was 3.6%-16.6%. Owing to limited human resources and skills in ultrasound, all studies mentioned the necessity of a universal screening system for the early detection of DDH. Conclusion Embedding universal ultrasound screening in community health checkup systems enables collaboration between healthcare professionals and caregivers to improve health inequities and ensure early detection of DDH cases.